The Influence of Financial Literacy and Peers on Financial Management with Self-Control as a Moderating Variable - Arina Hidayati; Nimas Aulia Pambajeng Miftahunnajah (Islamic Accounting Journal, 2025)
The purpose of this study is to analyze the influence of financial literacy and peers on financial management moderated by self-control. This study uses a quantitative approach in the form of numbers. The population of this study were 1,559 students of the Faculty of Economics and Business, Universitas Negeri Semarang, class of 2022. This study used a sampling technique in the form of simple random sampling with the Slovin formula and obtained 318 students as samples. The data collection technique in this study was through the distribution of questionnaires. The data was processed using Smart PLS 3 software. This study shows that there is a positive and significant relationship of financial literacy on financial management with a path coefficient value of 0.189, while peers have no effect on financial management with a path coefficient value of -0.078. There is a positive and significant influence of self-control on financial management with a path coefficient value of 0.539, but self-control cannot moderate the influence of financial literacy and peers on financial management. The results of this study can be an illustration for students in managing their finances and for further researchers can expand the research sample.